Animal models of human disease - Lange, Sigrun; Inal, Jameel (MDPI, 2023)
The use of animal models of human disease is critical for furthering our understanding of disease mechanisms, for the discovery of novel targets for treatment, and for translational research. This Special Topic entitled “Animal Models of Human Disease” aimed to collect state-of-the-art primary research studies and review articles from international experts and leading groups using animal models to study human diseases. Submissions were welcomed on a wide range of animal models and pathologies, including infectious disease, acute injury, regeneration, cancer, autoimmunity, degenerative and chronic disease. Seven participating MDPI journals supported the Special Topic, namely: Biomedicines, Cells, Current Issues in Molecular Biology, Diagnostics, Genes, the International Journal of Molecular Sciences, and the International Journal of Translational Medicine. In total, 46 papers were published in this Special Topic, with 37 full length original research papers, 2 research communications and 7 reviews. These contributions cover a wide range of clinically relevant, translatable, and comparative animal models, as well as furthering understanding of fundamental sciences, covering topics on physiological processes, on degenerative, inflammatory, infectious, autoimmune, neurological, metabolic, heamatological, hormonal and mitochondrial disorders, developmental processes and diseases, cardiology, cancer, trauma, stress, and ageing.